Analisis Jumlah Penempatan Kerja dan Beban Kerja dalam Meningkatkan Motivasi dan Produktivitas Kerja Karyawan PT. Bersih Sehat Cabang BSD, Bintaro, Puri Kencana, Menteng Tangerang Selatan dan Jakarta - Wahyudin Wahyudin; Ahmad Syukri (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
This study aims to analyze how the number of job placements and workload in increasing employee motivation and productivity at PT. Clean Healthy. With the unit of analysis are employees at PT. Clean Healthy. This study used descriptive qualitative research method. The data collection methods used were observation, documentation studies, and in-depth interviews with informants. The collected data is analyzed descriptively with the flow of documentation studies, reducing data, presenting data, drawing conclusions. In order to obtain the validity of the data, an analysis is carried out through the validity of trust, the validity of transferability, the validity of dependence, and the validity of certainty. From the results of this study, it can be concluded that from the results of interviews with key informants, the role of balance between the number of job placements and workload is very important in an effort to increase employee motivation and productivity at PT. Clean Healthy. Increasing motivation and work productivity is very important to strive for optimal achievement of company goals. Effectiveness and Efficiency are very important considerations in implementing a balance between the number of workers in each job placement position at PT. Clean Healthy with the workload delegated to every employee at PT. This Healthy Clean. Then from the results of interviews with informants, researchers found information that said that in some job placement positions at PT. Bersih Sehat is said to still be unbalanced in the number of workers. Then from the results of interviews with informants, researchers found information that said that in some job placement positions at PT. Bersih Sehat is said to have a workforce that is still not balanced with the workload it delegates. So that it can have an impact on increasing their motivation and work productivity. Thus PT. Bersih Sehat is considered necessary to review its application to the number of workers in each job placement so that it can be balanced with its workload as an effort to increase the motivation and work productivity of its employees.